NCS 613, a Potent PDE4 Inhibitor, Displays Anti-Inflammatory and Anti-Proliferative Properties on A549 Lung Epithelial Cells and Human Lung Adenocarcinoma Explants - Yougbare, Issaka; Belemnaba, Lazare; Morin, Caroline; Abusnina, Abdurazzag; Senouvo, Yannick F.; Keravis, Thérèse; Lugnier, Claire; Rousseau, Eric (Frontiers in Pharmacology, 2020)
Chronic inflammation is a deleterious process occurring in several pulmonary diseases; it is a driving force promoting tumorigenesis. By regulating local cyclic nucleotide concentration, cyclic nucleotide phosphodiesterases (PDE) govern important biological processes, including inflammation and proliferation. The aim of this study was to investigate the anti-inflammatory and anti-proliferative effects of NCS 613, a specific PDE4 inhibitor, on TNFα-treated human lung adenocarcinoma cell line (A549) and on human lung adenocarcinoma explants. PDE4 isoforms and inflammatory pathways mediated by p38 MAPK, ERK1/2 and IκBα were analyzed by Western blot and immunostainings. Proliferation were performed using [3H]-thymidine incorporation under different experimental conditions. TNFα-stimulation increased p38 MAPK phosphorylation and NF-κB translocation into the nucleus, which was abolished by NCS 613 treatment. Concomitantly, NCS 613 restores IκBα detection to normal level in human adenocarcinoma explants. An IC50 value of 8.5 μM was determined for NCS 613 on anti-proliferative properties while ERK1/2 signaling was down-regulated in A549 cells and lung adenocarcinoma explants. These findings shed light on PDE4 signaling as a key regulator of chronic inflammation and cancer epithelial cell proliferation. It suggests that PDE4 inhibition by NCS 613 represent potential and interesting strategy for therapeutic intervention in tackling chronic inflammation and cancer epithelial cell proliferation.